Enhancing Healthcare Efficiency: The Relationship between Effective Communication and Teamwork in Saudi Arabia - Ahmed Gh Alkordi Alghamdi; Khalid Turki Alkathlan; Fuz Hindi Al Otaibi; Zahrah Ali Hussein AL Hamar; Sarah Al Dosari; Sarah Mohammed Al ghamdi; Hammad Alaiyt M Alanazi; Manal Naser bin sunbil; Mehinatalobaidan; Lila Muteb Almutairi; Awatif Mohammed Darwish; Maha Mosleh Albugami; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
This article examines the critical relationship between effective communication and teamwork in Saudi Arabia’s healthcare system, emphasizing their role in enhancing efficiency, patient safety, and care quality. As part of Vision 2030, Saudi Arabia is transforming its healthcare sector, but challenges persist due to a multicultural workforce, linguistic diversity, and hierarchical structures. Drawing on research by Moussa et al. (2022) and others, this study highlights how communication barriers—such as language differences, cultural misalignments, and professional silos—contribute to medical errors and fragmented care. Conversely, effective teamwork, characterized by shared goals, mutual respect, and structured communication tools like SBAR, improves patient outcomes and operational efficiency. The article presents evidence-based strategies for improvement, including leadership commitment, interprofessional training, and technological innovations like AI-assisted communication. Case studies from Saudi hospitals, such as King Abdulaziz Medical City’s TeamSTEPPS implementation, demonstrate measurable success in reducing adverse events and boosting staff satisfaction. Policy recommendations advocate for national standards, language support programs, and teamwork metrics in quality monitoring. Ultimately, prioritizing communication and teamwork is essential for Saudi Arabia’s healthcare transformation. By addressing cultural and structural barriers, fostering collaborative environments, and leveraging technology, the system can achieve Vision 2030’s goals of high-quality, efficient, and patient-centered care.